A feminism of the soul? Postfeminism, postsecular feminism and contemporary feminine spiritualities - Poutiainen Ella (Sage Publications Ltd., 2025)
Increasingly popular ‘feminine spiritualities’ urge women to foster personal transformation and social change through spiritual empowerment and healing of ‘the feminine’. However, in spite of feminist undertones, feminism is rarely explicitly evoked, and is often even rejected. Gender scholars have debated over the ambivalent feminism of contemporary spiritualities, which are readily seen as closer to postfeminist rather than feminist ideals, or framed as a form of old-fashioned cultural feminism. While some recent analyses do explore the feminist potential of feminine spiritualities in more positive terms, the debates often lack practitioner perspectives on feminism and deeper considerations of the practitioners’ own self-definitions. Based on ethnographic interview material across Finnish and Anglo-American contexts, this article explores how adherents of feminine spirituality imagine feminism, and whether they consider their spirituality to be feminist or not and why. I argue that while practitioners hold varying, often ambiguous positions in relation to feminism, the narratives iterate shared themes that render feminism and feminine spirituality as incompatible: an emphasis on femininity over feminism, and a focus on spirituality instead of politics. Furthermore, practitioners critique mainstream feminism for being too secular, while often simultaneously agreeing with feminist criticisms of both cultural feminist and postfeminist ideals. I suggest that failing to take the voices of spiritual women into account prevents constructive dialogue and solidarity among secular and spiritual feminists as well as non-feminist women, and offers little room for emerging postsecular feminist identities.
Keywords
Affect, femininity, haunting, narrative analysis, postfeminism, postsecular feminism, spirituality